Structural Coupled Electromagnetic Sensing of Defects Diagnostic System - Ru, Gaige; Gao, Bin; Liu, Dong; Ma, Qiuping; Li, Haoran; Woo, Wai Lok (IEEE transactions on industrial electronics (1982), 2023)
Magnetic flux leakage (MFL) detection methods are widely used to detect pipeline defects. However, it is limited by the detection orientation and magnetization. Besides, bulky excitation systems are incapable of adapting to the complex detection environments. This article proposes a new electromagnetic structured coupling sensing of merging alternating current field measurement and MFL within a multiparameter system for different types of pipeline defects detection. In particular, a novel electromagnetic coupling sensor structure is proposed, which enables simultaneous interaction between the excitation modes of yoke and coil. Magnetic yoke is integrated to magnetizing the axial pipeline to detect the circumferential surface and subsurface defects while the coil excites the circumferential uniform alternating current field and recognizes the axial defect. The novel structured sensing is highly sensitive to the detection of both surface and subsurface defects. Simulation and experiments on defects in several samples have been conducted to validate the reliability and efficiency of the proposed system.